2014
DOI: 10.1007/s11096-014-9939-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of drug-related problems identified by clinical pharmacy staff at Danish hospitals

Abstract: The study found that a national database on DRPs contained multi-facetted DRPs, however evenly distributed for each of the 3 years. Even though the top 25 drugs were involved in 58 % of all DRPs, multiple drugs were associated with DRPs. The study emphasizes the importance of detecting and intervening for DRPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
3
13
1
1
Order By: Relevance
“…Similar results have been observed previously [5, 20, 30]. In addition, previous research shows that cardiovascular and psychotropic drugs contribute to hospitalisations due to adverse events in older people [6].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results have been observed previously [5, 20, 30]. In addition, previous research shows that cardiovascular and psychotropic drugs contribute to hospitalisations due to adverse events in older people [6].…”
Section: Discussionsupporting
confidence: 90%
“…These drugs, except hydroxyzine, also caused DRPs in previous research. Although hydroxyzine was not included as a specific substance in previous research, the association between DRPs and the drug class of anxiolytics has been observed [5, 20, 30]. The drugs that contributed most frequently to DRPs in this study can be attributed to different explanations.…”
Section: Discussionmentioning
confidence: 82%
“…Problems related to suboptimal pharmacotherapy such as untreated indications or inappropriate dosing regimens were also repeatedly identified. These findings correspond well with a characterisation from 2014 of medicine-related problems entered in a Danish national database 19. All clinical service in our study was provided by a single experienced clinical pharmacist (WBH) to give a consistent delivery of service, but this setup can, however, lower the generalisability of the results, which is a limitation in the study design.…”
Section: Discussionsupporting
confidence: 85%
“…The number of prescribed medicines at discharge as well as all written clinical recommendations were entered in a Danish national database of medicine-related problems 19. Acceptance of the clinical recommendations, defined as documented alteration in the medication regimens done by the physicians, was assessed by post look-ups in the medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical pharmacy services aim to provide comprehensive medication management that optimizes patient outcome . Many studies have emphasized the positive impact of clinical pharmacy services on the detection of drug‐related problems (DRPs) and patient outcome in various clinical settings . DRPs include all the issues that may interfere with the success of pharmacotherapy, and are closely linked to reduced clinical benefits of treatment and poor patient outcome .…”
mentioning
confidence: 99%